Total Innovative Management Excellence (TIME) : The Future of Innovation - Harrington, H. James, editor 428617; Voehl, Frank, 1946-, editor 553589 (New York, NY : CRC Press, Routledge, Taylor & Francis Group, 2020)
"Jim Harrington and Frank Voehl have gathered together the thoughts and ideas of more than 20 of the most creative innovation thought-leaders from business, professional practice, and academia in this compelling book. The thought leaders look at innovation from almost every angle -- Their statements offer an unparalleled view of innovation and provide a depth of insight that is extraordinary. Harrington and Voehl's reflection on each chapter, and on the sections within the book, provide useful links between themes and reinforce the relationships between many of the ideas. Anyone interested in innovation (practitioner or researcher) will benefit from this global thought collection. The contributors' multiple perspectives, models, practical examples, and stories provide a sense of innovation that no single writer could ever capture. A company's future growth will only come through successful innovation. This book is organized around six critical success factors supporting Total Innovative Management Excellence (TIME): Total Organization Context, Vision and Strategy, Leadership, Culture, Processes, and the Work Environment, as outlined in the new ISO Innovation Management Standards 56000 series. Three unassailable facts will strike you as soon as read this book: 1. Innovation is the new mantra; whether you're involved in teaching art and design, new product development for a blue-chip consumer brand or responsible for providing public services to citizens. 2. Understanding innovation requires multiple perspectives; from culture and mindset, social and commercial context, new ways of working as much as new products or services. 3. Innovation is a journey; drawing on insights from around the globe is essential to accelerate our progress"--